A meta-analysis of mannose-binding lectin gene polymorphisms with the risk of recurrent vulvovaginal infections - Namarta Kalia; Jatinder Singh; Akash Kumar Rauniyar; Manpreet Kaur (Nature Research, 2022)
The genetic variants of Mannose-Binding Lectin, a vital component of innate immunity have been studied with acute/recurrent vaginal infections ((R)VVI) and presented inconclusive findings. Therefore, a systematic review and meta-analysis of published data were conducted to assess the possible role of these variations in (R)VVI. A comprehensive search was made using PubMed, Web of Science and Google scholar till June 18, 2019. A total of 12 studies met the specified criteria and were included in the analysis. Different comparisons were made on the basis of the outcome of interest that resulted in the filtering of studies for the pooled analysis to find an association using the standard genetic models. Odds ratio (OR) with 95% confidence interval (CI) was chosen as the effect measure for the data synthesis. The trim and fill technique was applied to adjust the publication bias. The meta-analysis revealed the significant association (p < 0.05) of rs1800450 polymorphism with RVVI risk (OR ≥ 3.5) in all the genetic models. The subgroup analysis identified the same association in Caucasian and Mixed ethnicity. Quantitative synthesis based on RVVC showed>3.5 fold risk of disease development accredited to rs1800450. A combined evaluation of Exon1 variants showed no association with (R)VVI. This meta-analysis suggests rs1800450 polymorphism as a genetic predisposing factor for RVVI, but to reinforce, further studies with a larger sample size are warranted.